2010
DOI: 10.4038/tare.v10i0.1869
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Chemical Fertilizer for Land Management in the North-West Zone of Nigeria

Abstract: The study aimed at: (i)estimating the rates of adoption and application of inorganic fertilizer; and (ii)determining the farmer-and farm-characteristics conditioning the adoption of inorganic fertilizer in two selected States in the northwest zone of Nigeria, namely, Kano and Katsina States. A two-stage sampling procedure was adopted in the survey, First, two Agricultural Development Programme (ADP) zones were purposively sampled in each State on the basis of relative climate. In Kano State, Rano and Danbatta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…The adoption index ranges from 0 to 1 depending upon the farmer's degree of the technology adoption. The overall adoption indices of all the farmerswere categorised into four distinct categories (non-adopters, low adopters, medium adopters and high adopters) following Maiangwa et al (2007). The adoption score 0 point implies the non-adoption of the improved maize production package.…”
Section: Adoption Indexmentioning
confidence: 99%
“…The adoption index ranges from 0 to 1 depending upon the farmer's degree of the technology adoption. The overall adoption indices of all the farmerswere categorised into four distinct categories (non-adopters, low adopters, medium adopters and high adopters) following Maiangwa et al (2007). The adoption score 0 point implies the non-adoption of the improved maize production package.…”
Section: Adoption Indexmentioning
confidence: 99%
“…These States are considered representative in terms of biophysical characteristics and high agricultural production activities. In addition, these States have a high agricultural production potential, they were selected based on their high concentration on tomato production in the region with Kano being the most successful in Nigeria (Maiangwa et al, 2010). Multistage sampling techniques was used for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Younger farmers have been found to be more innovative and willing to bear risk, as opposed to older farmers (Asiabaka and Owens, 2002). However, Asante et al (2012), Wiredu et al (2011), andMaiangwa et al (2007) found a positive relationship between age and adoption. It is important that projects like the IPDM while targeting both older and young farmers, give priority to younger farmers because of their flexibility and willingness to try new things.…”
Section: The Determinants Of Ipdm Technology Adoptionmentioning
confidence: 96%
“…The argument is that larger households often have a lot of mouths to feed, to the extent that they do not have enough money to invest in technology adoption, as opposed to smaller families. In addition, farmers with relatively large family sizes attach greater importance to other non-farm activities than farm activities such as the adoption of IPDM technologies (Maiangwa et al, 2007;Amaza et al, 2008). On the contrary, Baffoe et al (2013), found a positive association between household size and adoption, arguing that larger families have greater labour force to be able to engage in the adoption of technologies.…”
Section: The Determinants Of Ipdm Technology Adoptionmentioning
confidence: 99%